Pengaruh Destinasi Agrowisata Kampung Melon Napote Terhadap Sosial Ekonomi Masyarakat di Desa Bira Timur Kabupaten Sampang - Nadifatul Lailiyah; Anas, Zulviar; Faisol, Faisol; Hanem Muntaha (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2025)
The Kampung Melon Napote Agrotourism Area is located in the Village of Monastery East, Sampang Regency, and is an area that has a strategic location for people to enjoy melon fruit tourism to their heart's content. The existence of this tourism development activity has an economic impact on the community, such as increased income, employment opportunities and business opportunities. The purpose of this study was to determine the impact of the agrotourism area on community income. The method used in this study is a qualitative method. This research includes field research. In obtaining direct information, the informants in this study were the owner of the melon village, the manager of the melon village agrotourism, and the community who participated in the management of the melon village agrotourism. Based on the results of the study regarding the Impact of the Agrotourism Area on Community Income, it has a positive impact caused by the Kampung Melon Npaote Agrotourism, namely an increase in income obtained from the existence of the agrotourism area. The difference in community income before and after the existence of this agrotourism can be seen from the turnover they get when this agrotourism is opened. The average income of the community after the existence of agrotourism is higher than before the existence of agrotourism. With this area, the community can increase their income through trade, provide parking services around the area and participate in managing orange groves. So it can be concluded that the existence of the agrotourism area can have an impact on increasing community income.